Pathogenesis of Keratoconus: The intriguing therapeutic potential of Prolactin-inducible protein. (November 2018) - Sharif, Rabab; Bak-Nielsen, Sashia; Hjortdal, Jesper; Karamichos, Dimitrios
Abstract: Keratoconus (KC) is the most common ectatic corneal disease, with clinical findings that include discomfort, visual disturbance and possible blindness if left untreated. KC affects approximately 1:400 to 1:2000 people worldwide, including both males and females. The aetiology and onset of KC remains a puzzle and as a result, the ability to treat or reverse the disease is hampered. Sex hormones are known to play a role in the maintenance of the structure and integrity of the human cornea. Hormone levels have been reported to alter corneal thickness, curvature, and sensitivity during different times of menstrual cycle. Surprisingly, the role of sex hormones in corneal diseases and KC has been largely neglected. Prolactin-induced protein, known to be regulated by sex hormones, is a new KC biomarker that has been recently proposed. Studies herein discuss the role of sex hormones as a control mechanism for KC onset and progression and evidence supporting the view that prolactin-induced protein is an important hormonally regulated biomarker in KC is discussed. Graphical abstract: Highlights: KC is a corneal thinning disorder appearing during puberty and leads to loss of visual acuity through ectasia, opacity, and scarring. The complex, multifactorial nature of KC and lack of a suitable animal model have hampered progress in KC studies. Engineered in vitro models combined with human biological samples enables investigation of KC pathobiology. Sex hormones play a critical role in maintaining the integrity of the human cornea, and act as control mechanisms for KC onset and progression. Ongoing efforts to develop targeted treatments for KC, led to identifying the Prolactin-Induced Protein (PIP), as a biomarker for KC.